Biventricular Morphology and Function Reference Values Derived From a Large Sample of Healthy Chinese Adults by Magnetic Resonance Imaging - Zhang, Zhen; Ma, Qiaozhi; Gao, Yiyuan; Cao, Lizhen; Zhu, Chengcheng; Zhao, Zhiwei; Zhao, Jun; Zeng, Linan; Lou, Mingwu; Pohost, Gerald M.; Li, Kuncheng (Frontiers in Cardiovascular Medicine, 2021)
Background: Quantification of cardiac structure and function is essential for diagnostic interpretation and clinical decision-making. We sought to establish cardiovascular magnetic resonance (CMR) reference values of left and right ventricular (LV and RV) morphology and function based on a large sample of healthy Chinese adults. Methods: 550 validated healthy Chinese adults (aged 21 to 70 years; 323 men) free of hypertension, diabetes, and obesity were included in this study. All the subjects were stratified by gender (men and women) and age decades. On cine CMR, measurements of biventricular end-diastolic, end-systolic, and stroke volumes (EDV, ESV, and SV), ejection fraction (EF), and end-diastolic LV wall thickness (LVWT) and mass (LVM) were obtained. Results: Men had greater LVEDV (111.6 ± 19.8 versus 94.6 ± 15.6 mL), LVESV (36.5 ± 9.8 versus 28.2 ± 7.9 mL), LVM (121.1 ± 19.9 versus 86.1 ± 14.5 g), global end-diastolic LVWT (8.1 ± 1.1 versus 6.7 ± 1.0 mm), RVEDV (128.0 ± 23.6 versus 101.7 ± 17.0 mL), and RVESV (53.5 ± 13.7 versus 36.8 ± 8.9 mL), while women had greater LVEF (67.5 ± 5.4 versus 70.4 ± 5.7%) and RVEF (58.5 ± 5.2 versus 64.0 ± 5.3 %) (all P < 0.001). For both men and women, age was negatively correlated with LVEDV (r = -0.31 and r = -0.32), LVESV (r = -0.37 and r = -0.47), RVEDV (r = -0.31 and r = -0.29), and RVESV (r = -0.33 and r = -0.44), while was positively correlated with LVEF (r = 0.28 and r = 0.43) and RVEF (r = 0.28 and r = 0.41) (all P < 0.001). Aging was associated with increasing global end-diastolic LVWT and LVM/LVEDV in both sexes (all P < 0.001). Older age was associated with increasing LVM only in women (r = 0.36, P < 0.001), not in men (r = 0.05, P = 0.359). Conclusions: We systematically provide age-, sex-, and body size-specific CMR reference values for biventricular morphology and function based on a large sample of healthy Chinese adults. Biventricular structure and function are significantly associated with age and sex.